2019
DOI: 10.1111/1471-0307.12589
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of lactic acid bacteria isolated from the Georgian, yoghurt‐like Matsoni

Abstract: Matsoni is a traditional Caucasian fermented milk product, characterised by a lactic acid bacteria (LAB) microbiota. Objectives of the present study were to isolate and identify the LAB of Matsoni samples collected from various Georgian areas and to study their technological characteristics. About 300 LAB from 71 samples of Matsoni were isolated and characterised. The species most representatives were Lactobacillus delbrueckii, Streptococcus thermophilus and Lactobacillus rhamnosus. This study highlighted a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Enterococci are found in the natural microbiota of many types of traditional dairy products specific to Turkey (Dagdemir and Ozdemir 2008;Ercan et al 2014;Kirmaci et al 2016). In this context, the presence of these bacteria in many traditional dairy products such as fermented dairy products suggested that these bacteria can be used as adjunct cultures in yoghurt production (Litopoulou-Tzanetaki et al 1984;Ghiamati et al 2016;Kakabadze et al 2019). This study aimed to use E. faecium and E. durans strains that are resistant to negative environmental conditions and known to have probiotic properties combined with starter yoghurt bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enterococci are found in the natural microbiota of many types of traditional dairy products specific to Turkey (Dagdemir and Ozdemir 2008;Ercan et al 2014;Kirmaci et al 2016). In this context, the presence of these bacteria in many traditional dairy products such as fermented dairy products suggested that these bacteria can be used as adjunct cultures in yoghurt production (Litopoulou-Tzanetaki et al 1984;Ghiamati et al 2016;Kakabadze et al 2019). This study aimed to use E. faecium and E. durans strains that are resistant to negative environmental conditions and known to have probiotic properties combined with starter yoghurt bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…2016; Kakabadze et al . 2019). This study aimed to use E. faecium and E. durans strains that are resistant to negative environmental conditions and known to have probiotic properties combined with starter yoghurt bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, even bacteria belonging to the same genus or species may exhibit dissimilar external features, including variations in enzyme production or substrate degradation processes [31]. For example, identification of Lactobacillus delbrueckii obtained from diverse sources revealed that different subspecies were present in each source, exhibiting distinct characteristics and activities of the bacteria [32]. That is why this study is necessary to test the plastic degradation of all isolated bacteria before applying the bacteria for use on a larger scale or in real environmental conditions.…”
Section: Molecular Identification Of Selected Plastic-degrading Bacteriamentioning
confidence: 99%
“…Several LAB strains with technological and probiotic properties are already applied in fermented milk. Nevertheless, there is an expanding need for new promising LAB strains since the market of functional dairy products is continuously asking for diversifying the available products (Kakabadze et al., 2019).…”
Section: Introductionmentioning
confidence: 99%